Criptoativos: entre a liberdade econômica e a intervenção estatal - Maciel, Igor Barbosa Beserra Gonçalves (2021)
This dissertation is about cryptoactives and the need for regulation. It was within a context of internet evolution, financial crises, and the search for an alternative means of payment, without the presence of a third-party intermediary, still with speed and privacy, that, in 2008, the first cryptoactive was born, that is, Bitcoin, which became known as the first cryptocurrency. The new electronic payment system caused a rupture in the current financial system, in which States, like Brazil, are holders of the power to issue forced coins. Since then, numerous other cryptoactives have emerged, with cryptocurrencies having gained prominence, which now total more than ten thousand in the market and are increasingly used. However, the lack of definition as to the legal nature of cryptoactives, as well as the inexistence of regulation around the world, stimulated the debate on whether to let them free or regulate them. In this motto, the problem is the investigation of the need to regulate cryptoactives, in order to make them compatible with economic development, not only due to the structural bias, but also due to the functional scope. As a theoretical foundation, it drew on: Bobbio (2009), Feitosa (2007), Nakamoto (2008), Nunes (2013), Smith (2009), Ulrich (2014), among others. For this purpose, the hypothetical-deductive approach method was used. Regarding the methodological procedure, the exploratory method was adopted. With regard to the research technique, this will be bibliographical-documentary. As for the objectives, there are: to present the general lines of cryptoactives; address economic development from the perspectives of free market and intervention, also address the current financial system and the new directions of capital; pointing out the uncertain environment related to cryptoactives, in addition to highlighting the current regulatory state in Brazil, reasoning about the need for regulation and exposing whether, between economic freedom and state regulation, there are ways to harmonize interests and how the sandbox regulatory framework can contribute to this. In terms of conclusions, it was asserted that a minimum of regulation for cryptoactives is interesting, to provide legal security, to avoid negative impacts on the economic development of States, especially in Brazil. In this context, the regulatory sandbox presents itself as an important instrument to reconcile cryptoactives with freedom, intervention, and multisignificant development. Other than that, regulation must consider the functional aspect of the law.